Post-Apartheid South Africa : The First Ten Years - Nowak, M. (International Monetary Fund, 2006)
This book provides a comprehensive review of recent economic developments in South Africa and the structural and policy challenges facing the authorities. Individual papers examine a range of topics such as unemployment and the labor market, recent trends in the private saving rate, the role of foreign direct investment in the development of South Africa's economy, the human and economic repercussions of the HIV/AIDS epidemic, the role of fiscal policy in economic stabilization, inflation developments, liberalization of trade and capital transactions, exchange rate developments, and lessons from the rand crises of 1998 and 2001.